Preliminary evaluation of the biological oxidation of thiocyanates. Progress report, November 30, 1977--February 28, 1978 - Neufeld, R.D.; Valiknac, T. (Pittsburgh Univ., Pa. (USA). Dept. of Civil Engineering, 1978)
Acclimated biological cultures were developed from activated sludge taken from coke plant biological waste treatment facilities. These cultures are capable of degrading potassium thiocyanate from an original concentration of 2000 mg/l SCN to less than 1 mg/l in an aeration period of 9 hours. pH inhibition appears to be significant at values greater than 7.6. Substrate inhibition occurs at concentrations of thiocyanate greater than 500 mg/l. Air stripping of thiocyanate does not appear to occur at neutral pH value. Preliminary assessments indicate that aerobic biological organisms may play a major role in the removal of aqueous thiocyanate as found in the wastewasters from the gasification of certain coals.